Analysis of total polysaccharides in gerigit mushroom (Schizophyllum commune) using phenol-sulfuric acid and freeze-drying methods - Irawan, Anry; Maretik, Maretik; Saparuddin, Saparuddin (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Edible mushrooms are used as a food source because they are low in fat, high in protein, and rich in vitamins. In addition to being a food source, mushrooms are known to have potential as immunomodulators for various diseases such as cancer, tumors, HIV, tuberculosis, and others. The substances in mushrooms that have potential as antitumor and immunomodulatory agents are polysaccharides. These polysaccharides possess immune-stimulating, anti-tumor, antioxidant, antibacterial, and antiviral activities. One example of an edible mushrooms is  gerigit mushroom (Schizophyllum commune). Until now, the research on Schizophyllum commune is still limited, especially regarding the quantitative determination of the amount of polysaccharides. This study aims to determine the total amount of polysaccharides in Schizophyllum commune from central Thailand using phenol-sulfuric acid and freeze-drying methods. Total polysaccharide concentration data were analyzed using absorbance data obtained from measurements of blank and standard samples on a spectrophotometer and analyzed using microsoft excel software. The results of this study indicate the presence of polysaccharides in Schizophyllum commune, which are characterized by the presence of orange color in the sample when phenol and sulfuric acid solutions are mixed. While for the concentration of total polysaccharides in the Schizophyllum commune samples FD1, FD2 and FD3 obtained consecutive results 42.5256 mg/g 33.7002 mg/g 36.6327 mg/g with an average of 37.62 mg/g. This study shows that gerigit mushrooms have potential as a source of bioactive compounds in the form of polysaccharides that can be used in the health sector